2015
DOI: 10.1039/c5nr01652e
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained modeling of vesicle responses to active rotational nanoparticles

Abstract: In recent years, magnetically-driven-rotating superparamagnetic nanoparticles have been emerging as a valuable component in designing targeted drug delivery carriers and cellular killers via membranes' physical rupture. The lack of an in-depth understanding of how to control the interaction of rotational nanoparticles (RNPs) with vesicles has hindered progress in the development of their relevant biomedical applications. Here we perform dissipative particle dynamics simulations to analyze the rotation frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The standard values σ = 3.0 and γ = 4.5 are used in our study [Zhang et al , 2015; Zhang and Wang, 2015a; 2015b]. The mass, length and time scales are all normalized in the DPD simulations, with the unit of length taken to be the cutoff radius r c , the unit of mass to be that of the solvent beads, and the unit of energy to be k B T .…”
Section: Computational Model and Methodologymentioning
confidence: 99%
“…The standard values σ = 3.0 and γ = 4.5 are used in our study [Zhang et al , 2015; Zhang and Wang, 2015a; 2015b]. The mass, length and time scales are all normalized in the DPD simulations, with the unit of length taken to be the cutoff radius r c , the unit of mass to be that of the solvent beads, and the unit of energy to be k B T .…”
Section: Computational Model and Methodologymentioning
confidence: 99%
“…As expected, cell membranes composed of amphiphilic lipids and membrane-associated proteins will be the main barrier to NP internalization. The pathway and efficiency of the internalization are highly related to the properties of the NPs, such as their size, shape, stiffness, and surface [29,30,31,32,33,34]. In short, to realize NP-mediated targeted drug delivery with high efficacy, it is necessary to carefully design the morphology and surface properties of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work indicated that cellular uptake of NPs coated with mixed hydrophilic/hydrophobic polymer ligands is strongly influenced by the patterning of such surface polymers . Another previous work of ours has demonstrated that magnetically driven rotating superparamagnetic cylindrical NPs can affect their local solvent environment and trigger different interactions with adjacent vesicles by controlling the rotating NPs’ shape, surface chemistry, and rotational frequency . However, the effect of NPs’ rigidity on their cellular uptake process remains poorly explored.…”
Section: Introductionmentioning
confidence: 95%